The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.cbpa.2019.110590
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-based assessment of the muscle maintenance and energy status of anurans from an extremely seasonal semi-arid environment, the Brazilian Caatinga

Abstract: Biomarker-based assessment of the muscle maintenance and energy status of anurans from an extremely seasonal semi-arid environment, the Brazillian Caatinga

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…It corroborates with the finding in aestivating anurans ( Cyclorana and Neobatrachus ) by Saymour (1973) , Withers (1993) , and Withers and Thompson (2000) with respect to decreased oxygen consumption and thyroid activity. Several studies have reported significant depression in aerobic metabolism rate during winter dormancy and aestivation in different anurans ( Storey and Storey, 1996 ; Hudson et al, 2006 ; Madelaire et al, 2020 ; Moreira et al, 2020 ). Unlike some anurans who endure dormancy in a hypoxic microhabitat and undergo anaerobic metabolic depression ( Rossi et al, 2020 ), toads like Sacphiopus couchii and frogs like Pleuroderma diplolistris , and Proceratophrys cristiceps follow aerobic metabolic depression in almost a normoxic microhabitat with air-filled chambers in sandy soil ( Seymour, 1973 ; Flanigan et al, 1990 ; Cervalho et al, 2010 ; Moreira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It corroborates with the finding in aestivating anurans ( Cyclorana and Neobatrachus ) by Saymour (1973) , Withers (1993) , and Withers and Thompson (2000) with respect to decreased oxygen consumption and thyroid activity. Several studies have reported significant depression in aerobic metabolism rate during winter dormancy and aestivation in different anurans ( Storey and Storey, 1996 ; Hudson et al, 2006 ; Madelaire et al, 2020 ; Moreira et al, 2020 ). Unlike some anurans who endure dormancy in a hypoxic microhabitat and undergo anaerobic metabolic depression ( Rossi et al, 2020 ), toads like Sacphiopus couchii and frogs like Pleuroderma diplolistris , and Proceratophrys cristiceps follow aerobic metabolic depression in almost a normoxic microhabitat with air-filled chambers in sandy soil ( Seymour, 1973 ; Flanigan et al, 1990 ; Cervalho et al, 2010 ; Moreira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating levels of androgens, corticosterone, and leukocytes, as well as the inflammatory response to immunological challenges, are suppressed during the dry season ( Madelaire and Gomes, 2016 ; Madelaire et al, 2017 ). More recently, adjustments in the regulation of energy turnover, protein synthesis, and proteostasis in the skeletal muscle of P. diplolister during estivation have also been described ( Madelaire et al, 2020 ). In brief, key biomarkers indicate the maintenance of aerobic capacity, suppression of protein synthesis, and activation of cell survival processes in the muscle of P. diplolister during the dry season ( Madelaire et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, adjustments in the regulation of energy turnover, protein synthesis, and proteostasis in the skeletal muscle of P. diplolister during estivation have also been described ( Madelaire et al, 2020 ). In brief, key biomarkers indicate the maintenance of aerobic capacity, suppression of protein synthesis, and activation of cell survival processes in the muscle of P. diplolister during the dry season ( Madelaire et al, 2020 ). These findings were interpreted as a strategy to limit the loss of musculoskeletal performance despite the long period of inactivity and lack of environmental resources ( Madelaire et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation